THE IMPACT OF SMARTPHONE USAGE IN ADOLESCENTS 15-24 YEARS OLD IN JABODETABEK REGION - Loveria Sekarrini (Universitas Airlangga, 2020)
ABSTRACT Youth and technology in the millennial era are inseparable. The need for technology makes smartphones the main needs that cannot be separated from the daily lives of youth. The use of smartphones has many benefits but not a few of its users experience addiction. Addiction on smartphones has different characteristics compared to other types of addiction. The aim of this study was to determine the description of smartphone addiction and the impact of physical, mental and sosial health in adolescents aged 10-24 years in Jabodetabek area. The research methodology used cross-sectional study with online survey of 118 respondents and focus on the characteristics of respondents, average usage time, time spent playing smartphones when they wake up, the purpose of using smartphones, the most frequently applications used, the impact of smartphone use. The results showed that almost half of the respondents experienced smartphone addiction at a moderate level (40.7%) and there were 16.9% who experienced severe addiction. The effects of smartphone addiction include problems with mild anxiety (45.8%) and complaints of hands, neck and eyes. Most complaints were on eye health problems such as watery eyes (73.7%), itching (70.3%) and blurred vision (66.1%). In addition, other complaints that many feel are in the hands such as tingling (67.8%) and wrist pain (31.4%). Excessive smartphone use has been shown to have an impact on physical health. For this reason, further research is needed to find out other health impacts both physically, mentally and sosially.Keywords: Smartphone Addiction, Addiction, Musculosceletal Disorder